Deforestation: Mapping the Impact on Wildlife - Ahlawat , Sonika (Trinity Law Review, 2024)
In the era of globalization, countries are making significant progress for the benefit of their populations. Governments are taking necessary steps to advance and provide facilities for the comfort of their citizens. However, amidst this progress, the welfare of wildlife is often overlooked. From a legal standpoint, wildlife lacks rights against governmental actions, and there is no provision for them to appeal against decisions, as they are not recognized as human beings. This article explores the multifaceted impact of deforestation on wildlife, emphasiz ing the profound consequences of habitat loss, disruption of food chains, and the sub sequent decline in biodiversity. As forests are systematically cut down, the intricate ecosystems that support various species face severe challenges, leading to number declines and, in some cases, species extinction. The article underscores the inter connectedness of ecosystems and the far-reaching implications of deforestation on climate change. In response to these challenges, conservation strategies such as sus tainable forestry practices, habitat protection, and the creation of wildlife corridors are discussed. In conclusion, the article calls for heightened awareness and collective action to preserve biodiversity and foster a harmonious coexistence between human activities and the natural world.